On some fossil Arthropoda from the Limeworks , Makapansgat, Potgietersrus - Kitching, J. W. (Bernard Price Institute for Palaeontological Research, 1980)
The fossil arthropod remains from the Limeworks deposit consist of puparial and dung ball casts from the Lower Phase I (Member 3) through to the Upper Phase I (Member 4) breccias. The puparial stages are represented in two gross sizes; cuticular remains and segmentation are evident in a few. Possible palaeoenvironmental implications based on the puparial remains and their state of preservation are briefly discussed. A remarkably well preserved fossilised juvenile centipede from the Lower Phase I (Member 3) breccia is placed on record for the first time.
Main article
Keywords: Arthropoda; Limeworks; Makapansgat